"Force-from-lipids" gating of mechanosensitive channels modulated by PUFAs. (March 2018) - Ridone, Pietro; Grage, Stephan L.; Patkunarajah, Amrutha; Battle, Andrew R.; Ulrich, Anne S.; Martinac, Boris
Abstract: The level of fatty acid saturation in phospholipids is a crucial determinant of the biophysical properties of the lipid bilayer. Integral membrane proteins are sensitive to changes of their bilayer environment such that their activities and localization can be profoundly affected. When incorporated into phospholipids of mammalian cells, poly-unsaturated fatty acids (PUFAs) determine the mechanical properties of the bilayer thereby affecting several membrane-associated functions such as endo- and exo-cytosis and ion channel/membrane receptor signalling cascades. In order to understand how membrane tension is propagated through poly-unsaturated bilayers, we characterized the effect of lipid saturation on liposome reconstituted MscS and MscL, the two bacterial mechanosensitive ion channels that have for many years served as models of ion- channel-mediated mechanotransduction. The combination of NMR and patch clamp experiments in this study demonstrate that bilayer thinning is the main responsible factor for the modulation of the MscL threshold of activation while a change in transbilayer pressure profile is indicated as the main factor behind the observed modulation of the MscS kinetics. Together, our data offer a novel insight into how the structural shape differences between the two types of mechanosensitive channels determine their differential modulation by poly-unsaturated phospholipids and thus lay the foundation for future functional studies of eukaryotic ion channels involved in the physiology of mechanosensory transduction processes in mammalian cells. Summary: Mechanosensitive channels MscL and MscS are differentially modulated by poly-unsaturated fatty acids in lipid bilayers. MscL becomes sensitized because of increased hydrophobic mismatch while MscS open state is stabilized due to changes in the bilayer lateral pressure profile determined by NMR. Graphical abstract: fx1